An Analysis Of Linguistic Politeness Strategies In Online Academic Communication - Istu Sri Poneni (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The rapid development of digital communication platforms has significantly transformed academic interaction, particularly in online learning and scholarly discourse. In online academic communication, linguistic politeness plays a crucial role in maintaining respectful interactions, minimizing misunderstandings, and fostering effective collaboration among participants. This study aims to analyze the types and functions of linguistic politeness strategies employed in online academic communication contexts, including virtual classrooms, academic discussion forums, and institutional communication platforms. Using a qualitative descriptive approach, data were collected from online academic interactions involving students and lecturers, such as discussion posts, chat messages, and email communications. The analysis is grounded in politeness theory, focusing on strategies such as positive politeness, negative politeness, bald-on-record, and off-record expressions. The findings indicate that positive politeness strategies are most frequently used to build rapport and solidarity, while negative politeness strategies are commonly applied to show respect and mitigate imposition in formal academic settings. However, instances of impoliteness and pragmatic failure were also identified, often caused by limited pragmatic awareness and the absence of non-verbal cues in online communication. The study highlights the importance of developing pragmatic competence and digital communication literacy among academic community members. It is expected that the findings will contribute to improving the quality of online academic communication by promoting awareness of appropriate linguistic politeness strategies in digital academic environments.